Cytotoxicity of the HpmA hemolysin and urease of Proteus mirabilis and Proteus vulgaris against cultured human renal proximal tubular epithelial cells. - Mobley, H L (1991)
Proteus mirabilis, a common agent of nosocomially acquired and catheter-associated bacteriuria, can cause acute pyelonephritis. In ascending infections, bacteria colonize the bladder and ascend the ureters to the proximal tubules of the kidney. We postulate that Proteus species uses the HpmA hemolysin and urease to elicit tissue damage that allows entry of these bacteria into the kidney. To study this interaction, strains of Proteus mirabilis and P. vulgaris and their isogenic hemolysin-negative (hpmA) or isogenic urease-negative (ureC) constructs were overlaid onto cultures of human renal proximal tubular epithelial cells (HRPTEC) isolated from kidneys obtained by immediate autopsy. Cytotoxicity was measured by release of soluble lactate dehydrogenase (LDH). Two strains of P. mirabilis inoculated at 10(6) CFU caused a release of 80% of total LDH after 6 h, whereas pyelonephritogenic hemolytic Escherichia coli CFT073 released only 25% at 6 h (P less than 0.012). Ten P. mirabilis isolates and five P. vulgaris isolates were all hemolytic and cytotoxic and produced urease which was induced by urea. The HpmA hemolysin is apparently responsible for the majority of cytotoxicity in vitro since the hemolysin-negative (hpmA) mutants of P. mirabilis and P. vulgaris were significantly less cytotoxic than wild-type strains. P. mirabilis WPM111 (hemolysin negative) was used to test the effect of urease-catalyzed urea hydrolysis on HRPTEC viability. In the presence of 50 mM urea, WPM111 caused the release of 42% of LDH versus 1% at 6 h in the absence of substrate (P = 0.003). We conclude that the HpmA hemolysin of Proteus species acts as a potent cytotoxin against HRPTEC. In addition, urease apparently contributes to this process when substrate urea is available.